Pemaknaan Khalayak Terhadap Keragaman Budaya Indonesia Dalam Musik Video Wonderland Indonesia 2 : The Sacred Nusantara (Chapter 2) Karya Alffy Rev - Rasyid Farhan Taufik, Mohammad; Lestari, Sri Budi; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Indonesia is renowned for its cultural diversity, encompassing various ethnic groups, languages, cultures, and religions. According to the 2010 Population Census by the Central Statistics Agency, there are 1,340 ethnic groups and 720 languages. However, the 2020 Population Census revealed a decline in the use of regional languages among the younger generation. This cultural diversity is showcased in the music video